Survival and Complications in Pediatric Patients With Cancer and COVID-19: A Meta-Analysis - Dorantes-Acosta, Elisa; Ávila-Montiel, Diana; Klünder-Klünder, Miguel; Juárez-Villegas, Luis; Márquez-González, Horacio (Frontiers in Oncology, 2021)
BACKGROUND: The pandemic caused by the novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has affected all age groups, including the pediatric population, in 3–5% of all cases. We performed a meta-analysis to understand the survival and associated complications in pediatric cancer patients as well as their hospitalization, intensive care, and ventilation care (supplemental oxygen/endotracheal intubation) needs. METHODS: A systematic search was performed using MEDLINE, TRIP Database, International Clinical Trials Registry Platform (WHO), The Cochrane Library, Wiley, LILACS, and Google Scholar. Additionally, a search using the snowball method was performed in Nature, New England Journal of Medicine, Science, JAMA, ELSEVIER editorial, Oxford University Press, The Lancet, and MedRxiv. Searches were conducted until July 18, 2020. A total of 191 cancer patients with coronavirus disease 2019 (COVID-19) were integrated from 15 eligible studies. In a sub-analysis, patients were stratified into two groups: hematological cancer and solid tumors. Outcome measures were overall survival, risk of hospitalized or needing intensive care, and need for ventilatory support in any modality. The random effects statistical analysis was performed with Cochran’s chi square test. The odds ratio (OR) and heterogeneity were calculated using the I2 test. RESULTS: The overall survival was 99.4%. There were no statistically significant differences in the risk of hospitalization between hematological malignancies and solid tumors (95% confidence interval [CI] 0.48–18.3; OR = 2.94). The risk of being admitted to the intensive care unit was also not different between hematological malignancies and other tumors (95% CI 0.35–5.81; OR = 1.42). No differences were found for the need of ventilatory support (95% CI 0.14–3.35; OR = 0.68). Although all the studies were cross-sectional, the mortality of these patients was 0.6% at the time of analysis. CONCLUSIONS: In the analyzed literature, survival in the studied group of patients with COVID-19 was very high. Suffering from hematological neoplasia or other solid tumors and COVID-19 was not a risk factor in children with cancer for the analyzed outcomes.